SPECIAL FINANCIAL PROVISIONS FOR SABAH UNDER THE FEDERAL CONSTITUTION: THE ISSUE OF THE 40% SPECIAL GRANT - Mazlianie Mohd Lan; Emeritus Professor Datuk Dr. Shad Saleem Faruqi (Journal of Malaysian and Comparative Law, 2025)
In the asymmetrical and consociational federal system of Malaysia, the special position of the Borneo States is prescribed in the Malaysian Federal Constitution. The financial provisions in the Federal Constitution, include exclusive assignment of special revenues and resources to the Borneo States. Specifically, the two-fifths or 40% Special Grant to Sabah under Article 112C and part IV of the Tenth Schedule of the Federal Constitution is popularly highlighted in recent times. This provision originates from the Malaysia Agreement 1963 and the Malaysia Act 1963. The implementation of the 40% Special Grant appears as a conundrum and will be deliberated on an analytical basis in this article. Before embarking on the discourse of the provisions of allocation of grants, revenue and the issue of the 40% Special Grant to Sabah, this article shall first discuss the special position of the Borneo States in the Federal Constitution. An analysis on the 40% Special Grant shall then be made. This article will address the relevant provisions on the 40% Special Grant including its review, the constitutional issues and the implementation of the 40% Special Grant through voyage of time, as well as an analysis of the Federal Estimates of Revenue and Expenditure from 1964 onwards. To address issues pertaining to the 40% Special Grant, several actions are recommended. Any dissensions pertaining to the issues of review of the 40% Special Grant or determination of revenue for purposes of calculation of the 40% Special Grant must be conciliated in strict compliance with the provisions of the Federal Constitution. Redress may be sought from different avenues such as appointment of an independent assessor, public litigation in the courts of law or political negotiations on mutual consensus.